Conceptualising the sociology of education: an analysis of contested intellectual trajectories. Issue 6 (17th August 2020) - Power, Sally; Rees, Gareth
Abstract: This paper presents an account of the development of the sociology of education in the UK, by means of an analysis of papers published in the field's flagship journal, the British Journal of Sociology of Education and its US equivalent, Sociology of Education. In particular, we examine the representation of two contrasting traditions in addressing social inequalities: 'political arithmetic'; and the more recent 'cultural turn'. We find that in the UK, the cultural turn dominates; whilst in the US, it is political arithmetic which does so. In accounting for these contrasting national profiles, we argue that they are underpinned by divergent social infrastructure and organisation. We also discuss some of the implications of the dominance of the cultural turn in the UK, specifically in terms of the relationship between the fields of academic research and policy and the development of a cumulative evidence base to address social inequalities in education.